(untitled) (Dissertare, 2018)
The objective of this paper is to describe the evolution of public policies for agricultural banking financing in Venezuela; and the behavior of the agricultural credit risk of the bank in the period 1995-2014. The research is quantitative, documentary and, mainly, descriptive; but, it includes elements of approximation to the relationship between variables mentioned before. The data was obtained by reviewing legal texts and reports from public and private entities in the country. The values ​​of the credit variables of the agricultural portfolio constitute national aggregates of the financial sector. Their analysis was based on comparative tables and time series, treated by descriptive statistics and correlation coefficients. These coefficients allowed us to approximate the relationship between agricultural financing policies and credit risk. In the same sense, stress testing methodology was used to visualize risk scenarios associated with these policies. Between 1995 and 2014, the fixing of the mandatory agricultural portfolio and interest rates tend to be concentrated in the hands of the State; As of 2005, the policies with credits for items and months of planting are deepened and specified. In the period studied there is an increase in the percentages of the agricultural portfolio, with a decrease in nominal and real interest rates. These correlate negatively with the total agricultural portfolio and positively with the delinquency rate. Three risk scenarios were identified that coincided with modifications in the financing policy. These results are indications of the link between credit risk and agricultural financing policy.